Ethnobotanical Study of Forest Tuber Plants as Local Food Resources in Sonraen, Indonesia - Bunyani, Nur Aini; Bait, Olivia Jihan Stifani; Roman, Maya F. (Jurnal Biologi Tropis, 2026)
Forest tuber plants are important non-timber forest products that contribute to local food security and the preservation of traditional knowledge in rural communities. However, the use of these indigenous food resources has declined due to changing dietary patterns and limited documentation of ethnobotanical knowledge. This study aimed to identify forest tuber species used as local food resources and describe their traditional processing practices in Sonraen Village, South Amarasi District, Kupang Regency, Indonesia. The research was conducted from 1–28 February 2026 using a descriptive ethnobotanical approach. Data were collected through field observations, exploration surveys, semi-structured interviews, documentation, and plant specimen identification. Five forest tuber species were identified: Dioscorea esculenta L., Colocasia esculenta L., Canna edulis Kerr (red and white varieties), and Dioscorea alata L. Dioscorea esculenta, Colocasia esculenta, and Dioscorea alata showed the highest citation frequency (20%), whereas white Canna edulis had the lowest (8%). Community knowledge of forest tuber utilization was categorized as good and has been transmitted across generations as part of local wisdom. Traditional processing includes washing, peeling, cutting, and boiling the tubers over wood-fired stoves before consumption as staple foods or rice substitutes. These findings demonstrate the potential of forest tubers as alternative local food resources and provide baseline data for developing food diversification programs based on local wisdom, while supporting biodiversity conservation and the sustainable management of non-timber forest products. Further studies on nutritional composition, cultivation, and value-added processing are recommended to promote their broader utilization.